Perancangan Media Pembelajaran Tata Surya Berbasis Multimedia dengan Metode Mind Mapping untuk Siswa Kelas IX SMP Muhammadiyah 3 Kaliwungu - Dimas Rahardian; Toni Wijanarko Adi Putra; Fitro Nur Hakim (STEKOM PRESS, 2020)
Based on the results of observation, the learning method used in SMP Muhammadiyah 3 Kaliwungu is in the form of discourse, discussions, question and answer with the book media. Learning methods that have been applied so far have not had enough impact on students' level of understanding. The method used is less successful, so students feel bored and bored. This study offers a solution for multimedia utilization with the Mind Map method as an interesting learning media, where computers can display text, images, videos and audio so that students can have a pleasant impression in the learning process. The validity value of media experts is 2.9 which is declared feasible, while the validity value of material experts is 3.3, which is declared feasible, and increases students' understanding and interest as users from 58.5% up to 80.5%.